Buddhist Integration to Promote Participation in Political Communication Among Local Politicians in Mueang District, Khon Kaen Province - (Chaimadee), Phramaha Payapnam Thitadhammo; Promgun, Suraphon; Huadsri, Chanchai (Journal of Graduate MCU KhonKaen Campus, 2025)
The objectives of this research were: 1) to examine the level of participation in political communication among local politicians in Mueang District, Khon Kaen Province; 2) to analyze the relationship between Buddhist principles leading to Right View (SammãDitthi) and local politicians' participation in political communication; 3) to propose a Buddhist-integrated approach to enhancing participation in political communication among local politicians. This study employed a mixed-methods research approach, consisting of: Quantitative research: Data was collected using questionnaires administered to a sample group of 197. Statistical analysis included frequency, percentage, mean, standard deviation, and hypothesis testing using Pearson’s correlation coefficient. Qualitative research: In-depth interviews were conducted with 12 key informants, and data were analyzed using descriptive content analysis. The research results were as follows: 1. The overall level of participation in political communication among local politicians was high, with a mean score of 4.14. When examined by specific aspects: Yonisomanasikãra (Wise Consideration) had the highest mean score (4.20). Paratoghosa (Listening to External Sources) followed with a mean score of 4.08. 2. Relationship between Buddhist principles and political communication participation; the study found that Buddhist principles leading to Right View (Sammã Ditthi) had a statistically significant positive correlation with the promotion of participation in political communication among local politicians, at the 0.01 significance level. The correlation coefficient (r) was 0.77, indicating a strong positive relationship. When analyzed by specific aspects: Paratoghosa (Listening to External Sources) and Yonisomanasikãra (Wise Consideration) both showed a statistically significant correlation with local politicians' participation in political communication at the 0.01 level. 3. Integration of Buddhist principles leading to right view (Sammã ditthi) to enhance political communication participation: the study suggests that local politicians should actively listen to public opinions and political suggestions. They should promote political awareness and understanding among citizens by utilizing online media platforms and public forums as channels for political communication. Politicians must carefully analyze, reflect on, and critically evaluate the information they receive before communicating it further. If any issues or errors arise from their communication, they should reevaluate and adjust their communication strategies to ensure accuracy and effectiveness.